Floristic composition and above-ground net primary production in natural grasslands on basaltic deep soils - Patricia Cecilia Basile Lorenzo; Daniel Formoso; Oscar Blumetto (Agrociencia Uruguay, 2021)
In natural grasslands of the basaltic region, livestock management is applied traditionally associated with continuous high stocking density resulting in the degradation of natural grasslands. Traditionally, aboveground net primary production (ANPP) was estimated from biomass cuts made in the fields. Today, it is possible to estimate ANPP using remote sensing techniques by synthetic images of enhanced vegetation index (EVI). Considering these, we aimed this study to: a) determine the effect of contrasting grazing managements on floristic composition, b) estimate the radiation use efficiency coefficient (RUE) and its seasonal variation, and c) determine the ANPP for two contrasting grazing methods. The experiment was carried out in five farms in the basaltic region of Uruguay with mixed grazing under natural grasslands from spring 2013 to summer 2015. Paddocks with contrasting livestock management were chosen in each site. Vegetation growth was measured using the re-growth technique with three exclusion cages. Floristic composition was estimated using the Braun Blanquet scale. RUE coefficient was estimated following the equation: ANPP = APAR×RUE, where APAR is the absorbed photosynthetically active radiation. Changes in the floristic composition, ANPP, and RUE coefficient were recorded throughout the study in the two treatments. The RUE data obtained will be used to estimate ANPP in natural grasslands more accurately.